An Introduction to the International ABS Regime and a Comment on its Transposition by the EU - Evanson Chege Kamau and Gerd Winter (Law, Environment and Development Journal, 2013)
This article summarises the core provisions of the ABS regime as required by the CBD and the NP. It identifies open questions and takes position concerning the interpretation of certain clauses. Looking at an exemplary transposition by a Contracting Party on the user side, it critically discusses the recent EU Commission Proposal for an ABS regulation.